Resposta crônica e aguda da glicemia a um protocolo de treinamento misto para melhora da saúde de diabéticos tipo 2 - Felício, Carlos Henrique Vieira (2008)
Characterized as a chronic dysfunction of the metabolism, genetic nature or fenótipica, that causes total or partial disability of insulin, the Diabetes Mellitus (DM) is a disease that prompted the Brazilian Society of Diabetes to classify it as an epidemic that is ongoing. The number of people with diabetes is growing because of the growth and aging population, greater urbanization, the increasing prevalence of obesity and inactivity, and the greater survival of the patient with DM. Currently, about 12 million of Brazilians are diabetics. Epidemiological data, estimate about 7.8 million people have the confirmed diagnosis with DM, due to aggressive changes in dietary habits and lifestyle of people, causing enormous reduction in levels of physical activity. For a long time the practice of physical activity is recommended for the treatment of individuals bearers of DM. Exercise promotes increase in the use of glucose and free fatty acids intra muscle and extra muscle for energy supply. The level of increase achieved, and the proportion of use of each substrate, is directly related to the intensity and duration of exercise, and is also influenced by the state of health, nutrition and the training of the individual. The goal of the research was to evaluate the effect of a training program of physical exercises mixed (aerobic / anaerobic conditioning circuit-break with active), including exercises, walking, weight training and Swiss ball, caused about possible changes in their metabolic system, as changes acute and chronic, individuals bearers of DM2. The methodology used is a model of experimented design of pre-test and post-test applied to the group. The blood glucose levels were analyzed in fasting pre-test and post-test, and capillary glycemia in three periods of physical exercise: pre, during and post training, and the statistical processing done by the use of Statistical Software for PC-For SPSS ® Windows ®, V. 12.0 .. With the result has been a drop in the values significant glucometers between 6 weeks of training, with a negative delta average of 68 mg / dl. Furthermore, similar results were also found variations in the daily glycemic between the moments before and after the training session acute. Thus we find that, regardless of the biological mechanism responsible, the program mixed aerobic and anaerobic conditioning circuit-break with active was effective in reducing and controlling chronic and acute glycemic of subjects type 2 diabetic. Key words: Diabetic’s Mellitus; glycemia; chronic and acute response; training.